Chrono-lume® and Magnesium Potentiate Aggregation of Canine but not Human Platelets in Citrated Platelet-Rich Plasma - Callan, Mary Beth; Shofer, Frances S.; Wojenski, Carol; Giger, Urs (Thrombosis and Haemostasis, 1998)
The effects of Chrono-lume® (CL) and magnesium sulfate (Mg2+), a component of this luciferin-luciferase reagent, on platelet aggregation were studied in platelet-rich plasma (PRP) obtained from blood anticoagulated with sodium citrate from humans, dogs, cats, horses, and cows. The final added Mg2+ concentration of both solutions ranged from 0.75-3.7 mM. CL and Mg2+ had no effect on maximum aggregation of platelets from humans induced by sub-threshold concentrations of collagen and ADP. In contrast, addition of CL or Mg2+ to canine PRP resulted in a dose-dependent and equal potentiation of platelet aggregation in response to sub-threshold concentrations of collagen, ADP, and thrombin in normal and thrombopathic dogs. The effect of CL on platelet aggregation induced by sub-threshold concentrations of agonists was less pronounced and varied in other species according to the agonist. The reason for the marked difference in sensitivity of human and canine platelets to CL or Mg2+ is not clear, although a difference in releasable cation pools of the platelets from these two species has been recognized. Platelet aggregation studies of animals with suspected thrombopathias should be performed without CL to prevent masking of a platelet function defect.